The general system for natural classification - Кашкаров, В.В. (Recent Contributions to Physics, 2016)
There are the results of study the general laws that arise in the quantitative description of the properties and relationships between objects of different nature. It is proposed to develop a method of expert estimations, based on relative estimates of the objects and the natural properties of the set of estimates as a whole. A new method of object’s classification reveals their structure and relationships sothe location of each object in this structure can be determined qualitatively. The results can be applied in many fields, wherethe methods of qualimetry used.